FAKTOR PENENTU TINGKAT PENGANGGURAN USIA PRODUKTIF AWAL PADA MASA PANDEMI COVID-19 DI KECAMATAN SUKAJADI - Althaf Azhar Rafhi Syahputra; Shafira Syahnaztia; Nurfahmiyati Nurfahmiyati (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
The Ministry of Manpower stated that the Covid-19 pandemic had a significant impact on labor market conditions in Indonesia. This is due to the increasing number of companies terminating their employees. With this, the unemployment rate increased by 7.35%. One of the factors that can affect the high unemployment rate is the high number of job seekers of 89% which is not matched by the number of jobs as many as 15 million that must be provided by the government. The purpose of this study was to determine what factors can determine the high rate of early productive age unemployment in Sukajadi District, Bandung City. The sample of this study were residents of early productive age located in Sukajadi District, Bandung City. The sampling technique used is purposive sampling. The method used is an exploratory quantitative method by performing regression analysis. The results of this study indicate that the variable level of education of early productive age and health level of early productive age have a significant effect on the unemployment rate of early productive age, while the variable of labor force participation rate of early productive age has no effect on unemployment rate of early productive age.